Antiphatogenic and Anti Food Spoilage Activities of Ethylacetate and Methanol Extract of Panax ginseng var. Notoginseng - SEDARNAWATI YASNI (Indonesian Society for microbiology, 2007)
Javanese ginseng is a traditional herb known to possess broad health benefits that have been clinically proven. The aim of this research was to analyze the antimicrobial activity of Javanese ginseng against pathogenic bacteria (Escherichia coli, Salmonella typhimurium, Bacillus cereus, Staphylococcus aureus), food spoilage bacteria (Bacillus stearothermophilus and Pseudomonas fluorescens) and food spoilage fungi (Aspergillus flavus, Fusarium graminearum, and Penicillium citrinum). The result may increase the utilization of ginseng not only for health purposes but also as a natural food preservative. It may also open new possibilities for the development of natural functional foods. Ethylacetate and methanol extracts, obtained by maceration, were fractionated employing vacuum liquid chromatography (VLC). Fractionation using methanol and ethylacetate as solvents produced six fractions from each solvent. Fractions 1 and 4 of methanol extract performed the highest growth inhibitory effects on Bacillus cereus (Gram-positive bacteria) and Escherichia coli (Gram-negative bacteria), whereas fractions 4 and fraction 5 of methanol extract effectively inhibited the growth of Penicillium citrinum.